Analisis Konten Buku Teks Fisika SMA pada Pokok Bahasan Rangkaian Listrik Searah - Maria Fransiska Tunga; Jumadi Jumadi (Postgraduate, University of Mataram, 2022)
This study aims to reveal the science process skills profile and the question type categories in physics textbooks for senior high school on the principle of direct current circuits. The research method in this study is descriptive analysis with a qualitative-quantitative approach. The sample of this research is two physics textbooks that refer to the 2013 curriculum which is generally used as learning resources in Senior High schools in Indonesia. The determination of the sample in this study is based on the purposive sampling technique. The results showed that book A and book B already contained all aspects of Science Process Skills (SPS) although with different percentages. The results also showed that the aspect that appears the most is